A Framework For Software Maintenance Model Development - Deraman, Aziz (Malaysian Journal of Computer Science, 1998)
The software maintenance process is one of the most costly activities within information system practice. The purpose of this paper is to address some of the difficulties in this process, by proposing a framework for the development of maintenance model. Essential to the software maintenance process is an ability to understand not only the software but the required changes as well. This can only be achieved where the relevant knowledge is available. Based upon this primary requirement, the proposed framework has made the knowledge as its basis for modelling other requirements for software maintenance model development. The framework first identifies the three operational elements, i.e. function, static entity and dynamic entity, required for general software maintenance process. With respect to the knowledge (as part of the dynamic entity components), the framework shows how these three operational elements should behave and interact amongst themselves to deliver a successful software maintenance model.